1996
DOI: 10.1037/0012-1649.32.2.263
|View full text |Cite
|
Sign up to set email alerts
|

Cardinality development and counting.

Abstract: Cardinality means that the last number word used in counting refers to the entire set of items and is thought to be crucial to correct counting. This research focuses on the cardinality acquisition and on the relation between cardinality and counting. Three groups of 24 children {3 years, 5 months to 5 years, 0 months) each received 4 kinds of tasks. First, they counted forward; then were shown sets that were counted for them backward sequentially, jumping forward in the sequence, or forward and backward; and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
1
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 12 publications
1
29
1
1
Order By: Relevance
“…Most researchers also agree that children learn the meanings of one, two, and three before they understand how counting is used to determine cardinality (e.g., that a set counted ''1-2-3-4" has four items) (Bermejo, 1996;Chi & Klahr, 1975;Descoeudres, 1921;Fuson, 1988;Klahr & Wallace, 1973;LeCorre & Carey, 2007;Schaeffer, Eggleston, & Scott, 1974;Wagner & Walters, 1982;Wynn, 1990Wynn, , 1992. These studies have shown that when young children are asked to name or produce very small sets, they do so without counting.…”
Section: Evidence From Counting Researchmentioning
confidence: 94%
See 1 more Smart Citation
“…Most researchers also agree that children learn the meanings of one, two, and three before they understand how counting is used to determine cardinality (e.g., that a set counted ''1-2-3-4" has four items) (Bermejo, 1996;Chi & Klahr, 1975;Descoeudres, 1921;Fuson, 1988;Klahr & Wallace, 1973;LeCorre & Carey, 2007;Schaeffer, Eggleston, & Scott, 1974;Wagner & Walters, 1982;Wynn, 1990Wynn, , 1992. These studies have shown that when young children are asked to name or produce very small sets, they do so without counting.…”
Section: Evidence From Counting Researchmentioning
confidence: 94%
“…They can match equivalent sets, label small numerosities, and use counting to determine cardinality (e.g., Bermejo, 1996;Bermejo & Lago, 1990;Fuson, 1988;Gelman & Gallistel, 1978;Huttenlocher, Jordan, & Levine, 1994;LeCorre & Carey, 2007;Mix, 1999;Mix, Sandhofer, & Baroody, 2005;Wynn, 1990). There have been different ideas about the origins of these skills-ideas that have generated abundant research on infancy and early childhood while largely ignoring toddlerhood (see Mix, Huttenlocher, & Levine, 2002, for a review).…”
Section: Introductionmentioning
confidence: 97%
“…Although an implicit understanding of cardinality and ordinality appears to emerge before children learn the sequence of number words (Bermejo, 1996;Brainerd, 1979;Brannon & Van de Walle, 2001;R. Cooper, 1984;Huntley-Fenner & Cannon, 2000;Ta'ir, Brezner, & Ariel, 1997;Wynn, 1990Wynn, , 1992b, the mapping of these concepts onto the counting sequence is an essential step in the development of arithmetical competencies.…”
Section: Cardinality and Ordinalitymentioning
confidence: 99%
“…Their performance is inconsistent and often influenced by factors other than cardinality. For small set sizes (e.g., less then 10), most children have a good grasp of cardinal value by 5 years (Bermejo, 1996;Freeman, Antonucci, & Lewis, 2000), but generalization to larger sets and a consistent focus on cardinality information over other information (e.g., perceptual cues) may not emerge for several more years (Piaget, 1965).…”
Section: Cardinality and Ordinalitymentioning
confidence: 99%
“…Sarnecka and Lee (2009) maintained that children with disability may appear as if they have mastered counting of numbers because they seem confident in reciting the counting sequence and repeating the last number word used in the count to answer the question "how many", but what this appearance might reflect is just an observational learning (Clements & Sarama, 2009). Bermejo, 1996;see Sadler and Faith (2009) confirmed that some young children had master cardinality principle; they go through phases of subset knowing. This might be due to less counting experience these children have due to their deficiency.…”
Section: Counting Proceduresmentioning
confidence: 99%